Pengaruh Peningkatan Power Otot Tungkai Terhadap Kecepatan Tendangan Lurus Tapak Suci Ekstrakurikuler SD Aisyiyah Kuningan - Deri Agustin; Didi Muhtarom (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to determine the significant increase in leg muscle power on the speed of straight kicks in the Tapak Suci extracurricular program at SD Aisyiyah Kuningan through plyometric barrier hops. The method used is a pre-experimental one-group pretest and posttest design. Data collection was conducted using the Vertical Jump test instrument and the straight kick test instrument developed by (Hidayat, 2021) with a reliability of 0.632 and a validity of 0.361. The t-test method was used for data analysis. The sample in this study consisted of students from the Tapak Suci extracurricular program at SD Aisyiyah Kuningan, using the saturated sampling technique. This study aims to examine the effect of increased leg muscle power on the speed of straight kicks in the Tapak Suci extracurricular program at SD Aisyiyah Kuningan. The results of this study indicate that there is a significant effect of leg muscle power training, specifically barrier hops, on the speed of straight kicks in the Tapak Suci extracurricular program at SD Aisyiyah Kuningan. The calculated t-value (t_hitung) of 2.447 is greater than the t-table value (t_tabel) of 1.703, with a significance level of 0.021, which is less than 0.05.